Peningkatan Overall Equipment Effectiveness (OEE) Pada Mesin Molding Melalui Perbaikan Six Big Losses Di PT. CWI - Eddy Eddy; Chairunissa Chairunissa (Universitas Teuku Umar, 2021)
TPM is an innovative approach to maintenance activities that focus on preventing damage to machines / equipment and preventing the occurrence of defective products related to machines / equipment. The success of implementing TPM can be measured from the Overall Equipment Effectiveness (OEE) value. OEE measures how effectively equipment is used and functions to keep equipment in ideal condition by minimizing six big losses. OEE consists of three main, measurable components: Availability, Performance and Quality. In this study, OEE calculations were carried out on Molding machines at PT. CWI. The results of OEE calculations for the period July 2019 to June 2020 ranged from 45.49% to 74.35%, indicating that the world class benchmark standard (85.0%) has not been achieved. Based on the loss analysis, it was identified that the dominant losses were Idling at 42.2%, Rework at 17.7% and Breakdowns at 17.3%. The three losses have the potential and become the main priority for improvement in the context of increasing OEE.